ПОРIВНЯЛЬНИЙ АНАЛIЗ ОСВIТНIХ СИСТЕМ ВЕЛИКОБРИТАНIЇ ТА УКРАЇНИ - Iгнатьєва Алiна (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статтi проаналiзована дiяльнiсть Я. Ряппо, який знайшов прогалини в навчаннi в Українi. Цей проект проаналiзував Я. Ряппо, який вiдзначив, що система українського навчаня вiдрiзняється вiд iнших систем освiти в свiтi, зокрема Великобританiї, виокремив зв’язок iнших педагогiв Британiї у ХХ ст. Протягом ХХ столiття були вивченi свiтовi органiзацiї, якi iнiцiювали iнтеграцiйнi процеси в навчальнiй сферi задля головної мети – пiдвищення її ефективностi. Європейські фахівці висловлюють думку про те, що сьогодні якісна освіта не може обмежуватися лише набуттям умінь читати, писати, рахувати, натомість вона повинна охоплювати досить широкий спектр соціально-технологічних знань, умінь і навичок – комп’ютерна, екологічна, політична грамотність. В статье проанализирована деятельность Я. Ряппо, который нашел пробелы в обучении в Украине. Этот проект проанализировал Я. Ряппо, который отметил, что система образования Украины отличается от других систем образования в мире, особенно Великобритании, выявил связь других педагогов Британии в ХХ в. В течении ХХ века были изучены мировые организации, которые инициировали интеграциооные процессы в образовательной сфере для главной цели – повышения еë ефективности. Европейские специалисты рассказывают о том, что сегодня качественное образование не может ограничиваться только приобретениями уметь читать, писать, считать, к тому же, оно должно охвачивать широкий спектр социально-технологических знаний, умений и навыков – компьютерная, экологическая, политическая грамотность. This essay related about Yan Ryappo’s activity, who was organized in the field of education in Ukraine. The project of educational system made by Ryappo is analyzed, Ukrainian and Russian systems of overall labour high professional schools were differentiated, related about others Britain’s pedagogues in XX century. During XX century were educated universal organizations, which initiated internationals processes in educational sphere with aim of rising her effectiveness. In modern conditions demands to education begin width, than passing of complex discipline knowledge’s, from education we waiting training to life, formation readiness to continuous education. European specialists to tell, that quality education can’t limited only acquisitions to read, to write, to count, also can envelop widely spectrum of social- technological knowledge’s, ability and skills – computers, ecological, political literacy. Expressed recommendations include to necessary contents education block of knowledge’s as: protection of environment, antiracism education, studying local dialects, sexual education, protection of health, rational feeding, problems of population, prevention of alcoholism, drug addition etc.